2017
DOI: 10.1155/2017/5806236
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of IL-4 −590 (C>T) Gene in Iraqi Asthma Patients

Abstract: This study is the first investigation in Iraq dealing with genotyping of IL-4 −590 (C>T) gene, especially in Iraqi patients with asthma. We studied forty-eight blood samples collected from patients with asthma and compared with age-matched 25 healthy individuals as controls. The polymorphism results of IL-4 −590 (C>T) gene by using amplification refractory mutation system (ARMS-PCR) showed the presence of C and T alleles and three genotypes (CC, CT, and TT). Interestingly the frequency of C allele and CC genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
(21 reference statements)
0
13
0
1
Order By: Relevance
“…In the current meta-analysis, 818 asthma patients and 831 healthy individuals participated in these 8 independent case-control studies [ 18 , 19 , 21 25 ]. In Table 1 , the genotype distribution and detailed characteristics of the selected studies about the relationship between the polymorphism of IL-4-590C > T and the susceptibility to asthma are displayed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current meta-analysis, 818 asthma patients and 831 healthy individuals participated in these 8 independent case-control studies [ 18 , 19 , 21 25 ]. In Table 1 , the genotype distribution and detailed characteristics of the selected studies about the relationship between the polymorphism of IL-4-590C > T and the susceptibility to asthma are displayed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the polymorphism of IL-4-590C > T gene in the risk of asthma has not been clearly concluded. The study of Hussein et al [ 21 ] showed that the increased susceptibility to asthma was associated with the C allele and CC genotype of IL-4-590C > T gene polymorphism, which was considered to be the etiological part of asthma. However, it was found that the higher the percentage of T allele in the control group, the lower the susceptibility to asthma [ 18 , 19 , 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of asthma, the identification of susceptible genes that are involved in asthma pathogenesis and treatment response is the first step towards developing personalized medicine 10,11. Genome-wide association studies, candidate-gene linkage studies, and positional cloning have already discovered a large number of genetic variants in multiple genes that have been associated with altered therapeutic response to asthma medications and hence affect the level of asthma control 5,10,11. The ADRB2 gene is one of the most widely studied asthma susceptible genes 12,13.…”
Section: Introductionmentioning
confidence: 99%
“…One of the core factors of asthma attack is the high activation of Th2, and IL-4 plays an important role as the key component of Th2 activation. The function of IL-4 is related to multiple factors, among which the -589C/T polymorphism has been widely studied (24).…”
Section: Mechanisms Of Asthmamentioning
confidence: 99%